Meroterpenoids with Immunosuppressive Activity from Edible Fungus Craterellus odoratus - Quan Dai; Li-Ting Pang; Fa-Lei Zhang; Gang-Qiang Wang; Xue-Mei Li; Ji-Kai Liu; Tao Feng (Molecules, 2023)
Two unusual polyketide–sesquiterpene metabolites, craterodoratins T (1) and U (2), along with the known compound craterellin A (3), were isolated from the higher fungus Craterellus odoratus. The structures of isolated compounds were characterized based on nuclear magnetic resonance (NMR) and mass spectrum (MS) spectroscopic analysis, while the absolute configuration of the compounds was determined by theoretical NMR and electronic circular dichroism (ECD) calculations. Compound 1 possessed a rare structure with two aromatic groups. Compounds 1 and 3 showed immunosuppressive activity with IC50 values ranging from 5.516 to 19.953 μM.